User Experience Improvement with Learning Media using Dance Pads for Mentally Challenged Children - Sagirani, Tri; Edi Nugroho, Lukito; Insap Santosa, Paulus; Kumala, Amitya; ., . (International Journal of Engineering and Technology, 2019)
User experience is accentuated to ensure that the learning media suit the students. Six students with disabilities were engaged in compiling this paper. They were diagnosed with mild mental retardation. These students were learning how to concentrate and move their fingers and footstepf in order to be able to reach a certain place. The visualization of the street, fence, and house make this learning media more fascinating to be used. User experience was established by the interaction of the users and the learning media. The interaction was built by the movements of the studentsâ€™ fingers and footstep. The movements of the fingers were facilitated by arrow keys from keyboard, while the movements of the footstep were facilitated by dance pads. The results show that learning media using dance pads provide the average time improvementÂ of 27% faster and more accurate than the motions of the fingers using keyboard. In terms of the attractiveness and interests of children against learning media, 71% of the students expressed this media interesting, 14% of them found it difficult to use, and the rests did not provide any feedbacks. Learning media designed using dance pads can be explore, entertain and make effective learning. Dance pads can be used not only for playing popular game, but also for helping students with special needs to learn.Â Â